PENGARUH UTANG LUAR NEGERI TERHADAP EKONOMI POLITIK NEGARA INDONESIA - Dwitiya Putri Kirana, Geraldine; Yulhendri; Lince Magriasti (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2025)
The initial aim of this research is to describe how Indonesia's foreign debt has developed, how it affects Indonesia's political economy, and what alternative policies can be used to reduce the detrimental impact on the country's economy. The research method used is literature and qualitative studies. Literature research to produce quality data. Several government institutions, including Bank Indonesia, Central Statistics Agency, Ministry of Foreign Affairs, and Ministry of Finance of the Republic of Indonesia, provided research data. The research results show that: 1) Foreign Debt (ULN) can accelerate Indonesia's economic growth in industries that use a lot of debt. 2) The government can utilize foreign debt for its interests in the political field, especially in terms of conducting campaigns. 3. The importance of domestic savings is expanding. 3) A third option to address significant foreign debt is an exchange program.